IgA Response to ESAT‐6/CFP‐10 and Rv2031 Antigens Varies in Patients With Culture‐Confirmed Pulmonary Tuberculosis, Healthy Mycobacterium tuberculosis–Infected and Non‐Infected Individuals in a Tuberculosis Endemic Setting, Ethiopia. (22nd August 2013) - Legesse, M.; Ameni, G.; Medhin, G.; Mamo, G.; Franken, K. L. M. C.; Ottenhoff, T. H. M.; Bjune, G.; Abebe, F.
Abstract: Little attention has been given to the role of antibodies against Mycobacterium tuberculosis (Mtb) infection. We have compared the levels of IgA and IgG against ESAT‐6/CFP‐10 and Rv2031c antigens in sera of patients with culture‐confirmed pulmonary tuberculosis (PTB), healthy Mtb‐infected and non‐infected individuals in endemic TB settings. Venous blood samples were collected from 166 study participants; sera were separated and assayed by an enzyme‐linked immunosorbent assay (ELISA). QuantiFERON‐TB Gold In‐Tube (QFTGIT) assay was used for the screening of latent TB infection. The mean optical density (OD) values of IgA against ESAT‐6/CFP‐10 and Rv2031 were significantly higher in sera of patients with culture‐confirmed PTB compared with healthy Mtb‐infected and non‐infected individuals ( P < 0.001). The mean OD values of IgG against ESAT‐6/CFP‐10 and Rv2031 were also significantly higher in sera of patients with culture‐confirmed PTB compared with healthy Mtb‐infected and non‐infected individuals ( P < 0.05). The mean OD values of IgA against both antigens were also higher in sera of healthy Mtb‐infected cases compared with non‐infected individuals. There were positive correlations ( P < 0.05) between the level of IFN‐γ induced in QFTGIT assay and the OD values of serum IgA against both antigens in healthy Mtb‐infected subjects. This study shows the potential of IgA response against ESAT‐6/CFP‐10 and Rv2031 antigens in discriminating clinical TB from healthy Mtb‐infected and non‐infected cases. Nevertheless, further well‐designed cohort study is needed to fully realize the full potential of this diagnostic marker.